2012
DOI: 10.4028/www.scientific.net/amr.488-489.847
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Proper Conditions in Face Milling Palmyra Palm Wood and Coconut Wood Using Design of Experiment

Abstract: The purpose of this research was to investigate the effects of main factors on the surface roughness in face milling process palmyra palm wood and coconut wood by computer numerical controlled milling machine and using shell end mill cutting tools 6 edges. The main factors including speed, feed rate, depth of cut and angle of cut were investigated for the optimum surface roughness. The result of preliminary trial showed that the depth of cut and the angle of the cut had no effect on surface roughness. It was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In a previous study, the feed rate was defined as the time the material was subjected to the cutting process, and it was stated that a decrease in the feed rate means that a point on the material is in contact with the end mill tool for a longer time (Pelit and Yaman 2020). It has also been reported in previous studies that the surface roughness values of wood or wood-based materials machined with a CNC router machine increase due to increasing feed rate, and the surface quality decreases (Mitchell and Lemaster 2002;Iskra and Tanaka 2005;Davim et al 2009;Karagöz 2010;Rawangwong et al 2011;Kaya et al 2017).…”
Section: Fig 6 Roughness Values Of Thermally Treated Beech Wood Samples Cut With Different Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the feed rate was defined as the time the material was subjected to the cutting process, and it was stated that a decrease in the feed rate means that a point on the material is in contact with the end mill tool for a longer time (Pelit and Yaman 2020). It has also been reported in previous studies that the surface roughness values of wood or wood-based materials machined with a CNC router machine increase due to increasing feed rate, and the surface quality decreases (Mitchell and Lemaster 2002;Iskra and Tanaka 2005;Davim et al 2009;Karagöz 2010;Rawangwong et al 2011;Kaya et al 2017).…”
Section: Fig 6 Roughness Values Of Thermally Treated Beech Wood Samples Cut With Different Parametersmentioning
confidence: 99%
“…It has been reported that high spindle speed and low feed rate decrease the surface roughness of wood in pocket machining with a CNC router machine, and therefore the spindle speed and feed rate considerably affect the surface quality (Davim et al 2009;Karagöz 2011). In previous studies in which surface roughness was determined after processing different materials (wood, wood-based, or composite) with a CNC router machine, increases in the spindle speed reduced the roughness of the machined surface and increased the surface quality (Rawangwong et al 2011;Aghakhani et al 2013;Sütçü and Karagöz 2013;Patel and Patni 2014;Kaya et al 2017).…”
Section: Fig 6 Roughness Values Of Thermally Treated Beech Wood Samples Cut With Different Parametersmentioning
confidence: 99%
“…Differences also exist when these materials are compared to solid wood. A better understanding of the necessary process parameters to cut these materials will lead to the improved results with respect to tool wear and surface roughness [2][3][4][5][6][7][8]. Researchers have attempted to gain more understanding in wood machining process.…”
Section: Introductionmentioning
confidence: 99%